Application Integration for Sustainability Smart Tourism Model in Indonesia - Meiyanti, Ruci (Tech-E, 2023)
The existence of the COVID-19 pandemic over the past few years has made the tourism world slump, and Indonesia is no exception. However, this creates a potential use of IT not only for managing tourism activities but also for managing risks and conflicts that arise due to pandemics or others. The existence of various integrated managements on the economic, socio-cultural, and ecological dimensions can create tourism sustainability that is supported by technological advances. The purpose of this study is to provide a comprehensive and integrated model of sustainable tourism activities supported by the use of IS/IT infrastructure. The methods used in the formation of this model are Interpretative Structural Modeling (ISM) and smart thinking. From ISM, four key components are produced, namely innovation, local wisdom, local residents resources, and revitalization of tourist destinations due to disasters. The results of this study are in the form of a smart tourism sustainability model in Indonesia which is supported by an integrated application derived from the four key components